2023
DOI: 10.1080/19490976.2023.2281011
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate reduces adherent-invasive E. coli -evoked disruption of epithelial mitochondrial morphology and barrier function: involvement of free fatty acid receptor 3

Samira A. Hamed,
Armaan Mohan,
Saranya Navaneetha Krishnan
et al.

Abstract: Gut bacteria provide benefits to the host and have been implicated in inflammatory bowel disease (IBD), where adherent-invasive E. coli (AIEC) pathobionts ( e.g ., strain LF82) are associated with Crohn’s disease. E. coli -LF82 causes fragmentation of the epithelial mitochondrial network, leading to increased epithelial permeability. We hypothesized that butyrate would limit the epithelial mitochondrial disruption caused by E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For example, butyrate can reduce the aggregation of neutrophils, thus ameliorating DSS-induced colitis in mice [85]. Recently, it was shown that butyrate can also ameliorate increased intestinal epithelial permeability induced by AIEC pathobionts (e.g., strain LF82) in UC and maintain the normal morphology and function of epithelial cell mitochondria [86]. Huc-MSCs can upregulate the levels of SCFA-producing bacteria, including Akkermansia, Faecalibaculum, and Clostridia_UCG_014, in the IBD model, which, in turn, promotes T cell homeostasis, thereby alleviating the inflammatory state of the intestinal mucosa [87].…”
Section: Directly Affecting Specific Strainsmentioning
confidence: 99%
“…For example, butyrate can reduce the aggregation of neutrophils, thus ameliorating DSS-induced colitis in mice [85]. Recently, it was shown that butyrate can also ameliorate increased intestinal epithelial permeability induced by AIEC pathobionts (e.g., strain LF82) in UC and maintain the normal morphology and function of epithelial cell mitochondria [86]. Huc-MSCs can upregulate the levels of SCFA-producing bacteria, including Akkermansia, Faecalibaculum, and Clostridia_UCG_014, in the IBD model, which, in turn, promotes T cell homeostasis, thereby alleviating the inflammatory state of the intestinal mucosa [87].…”
Section: Directly Affecting Specific Strainsmentioning
confidence: 99%
“… 179 Furthermore, organoids models are employed for evaluating repurposed drugs originally intended for other diseases and assessing their efficacy against novel diseases. 180 , 181 They also serve as a means to continuously identify new targets and design targeted therapy strategies. 182 , 183 , 184 , 185 Organoids models also facilitate the exploration of alternative treatment approaches for challenging drug targets.…”
Section: Organoids Models In Clinic: Gi Disease Simulation and Treatmentmentioning
confidence: 99%
“…Therefore, decreased abundance of butyrate‐producing bacteria in IBD would contribute to loss of epithelial mitochondrial and barrier functions, which could further trigger disease and/or exacerbate a low‐grade inflammation. 180 …”
Section: Organoids Models In Clinic: Gi Disease Simulation and Treatmentmentioning
confidence: 99%